Modelo de cuidado para el desarrollo sostenible en comunidades rurales del Perú - Rodríguez, María (2018)
Descriptive study, exploratory, multicenter, qualitative of critical cutting-dialectical, whose objective is to propose a model of care for the sustainable development of rural communities in Peru. The scenarios of study are three rural communities of the regions Amazons, La Libertad and Moquegua, where families and social actors will be interviewed by means of the Questionnaire Sustainable Human Development (SHD) and guide the Focal Group respectively, information that will be used in the preparation of the care model for sustainable development in rural communities. It presents an advance of the characterization of the sustainable development of the rural community Dos de Mayo, pertaining to the region Amazons, through aspects for the sustainable development of the Community referred by positive indicators and social actors of the social and cultural determinants identified in families: the economic position of mothers is the trade 20% and of the parents, the agriculture 72.5%; they have own house 75%, drain 85%, water tubed 97.5%; they have knowledge of the medicinal use of plants and use them to treat their health problems. The model of care to starting from the capacities of the community into the management of its development in a sustainable manner.